2023
DOI: 10.1126/sciadv.add9031
|View full text |Cite
|
Sign up to set email alerts
|

Marine biogenic emissions of benzene and toluene and their contribution to secondary organic aerosols over the polar oceans

Abstract: Reactive trace gas emissions from the polar oceans are poorly characterized, even though their effects on atmospheric chemistry and aerosol formation are crucial for assessing current and preindustrial aerosol forcing on climate. Here, we present seawater and atmospheric measurements of benzene and toluene, two gases typically associated with pollution, in the remote Southern Ocean and the Arctic marginal ice zone. Their distribution suggests a marine biogenic source. Calculated emission fluxes were 0.023 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 91 publications
(165 reference statements)
0
11
1
Order By: Relevance
“…As a result, uncertainty in the vertical distributions of chlorophyll and isoprene concentration under sea surface microlayer may lead to the uncertainty in the estimation of marine isoprene emission. Furthermore, previous observations detected notable VOCs emissions in the Arctic region and highlatitude South Ocean during winter (Abbatt et al, 2019;Wohl et al, 2023). These emissions may be underestimated in our model due to the limitations of satellite data.…”
Section: Data Uncertaintiesmentioning
confidence: 66%
“…As a result, uncertainty in the vertical distributions of chlorophyll and isoprene concentration under sea surface microlayer may lead to the uncertainty in the estimation of marine isoprene emission. Furthermore, previous observations detected notable VOCs emissions in the Arctic region and highlatitude South Ocean during winter (Abbatt et al, 2019;Wohl et al, 2023). These emissions may be underestimated in our model due to the limitations of satellite data.…”
Section: Data Uncertaintiesmentioning
confidence: 66%
“…In recent years, multiple studies have reported that isoprene and other VOCs are emitted in marine environments at higher rates than previously thought 24,25,31 . This could help explain the observed concentrations of VOC oxidation products and aerosol precursors, such as glyoxal and methylglyoxal, from marine sources 32,33 , and help close the OH budget over marine regions 34 .…”
Section: Discussionmentioning
confidence: 91%
“…A potential driver of this low bias is the suppression of OH by other VOCs present in the atmosphere but not included in the simulations 24,25 . However, we ruled this out with simulations where a dummy species, which reacts with OH at half the rate of OH+isoprene and does not regenerate OH, is included with the same (TI_MI_-MEAN_D_sink) and 100 times (TI_MI_MEAN_D_sink_100x) the emissions of marine isoprene.…”
Section: Model -Observation Comparisonsmentioning
confidence: 99%
“…In recent years, multiple studies have reported that isoprene and other VOCs are emitted in marine environments at higher rates than previously thought 24,25,31 . This could help explain the observed concentrations of VOC oxidation products and aerosol precursors, such as glyoxal and methylglyoxal, from marine sources 32 , and help close the OH budget over marine regions 33 .…”
Section: Future Directionsmentioning
confidence: 91%